Pre-Service Elementary Teachers’ Difficulties in Solving Mathematical Problems Containing Contradictory Information - Hadi, Fida Rahmantika; Ardianzah, Ferri (JMPM: Jurnal Matematika dan Pendidikan Matematika, 2025)
This study investigates the difficulties experienced by pre-service elementary teachers in solving mathematical problems containing contradictory information. Such problems require reflective reasoning and verification beyond procedural fluency. Using a qualitative descriptive case study, 33 fifth-semester students from the Elementary Teacher Education program at Universitas PGRI Madiun participated. Data were collected through problem-solving tests, think-aloud protocols, and interviews, and analyzed through reduction, display, and conclusion drawing with triangulation. The findings revealed three interrelated types of difficulties: cognitive, metacognitive, and affective. Cognitive difficulties dominated as students relied on formulas without validating data accuracy; metacognitive difficulties appeared in poor regulation and limited strategy adjustment; while affective difficulties involved anxiety and low confidence. The study highlights that students’ challenges extend beyond conceptual understanding and suggests integrating contradictory-information tasks and metacognitive scaffolding to promote reflection and resilience in teacher education.